Post-exposure prophylaxis following high-risk contact with Ebola virus, using immunotherapies with monoclonal antibodies, in the eastern Democratic Republic of the Congo: an emergency use program. (December 2021) - Jaspard, Marie; Juchet, Sylvain; Serra, Béatrice; Mayoum, Baweye; Kanta, Issa Malam; Camara, Mohamed Seto; Mbala, Placide; Kojan, Richard; Malvy, Denis
Highlights: Measures have to be taken to avoid contamination of Ebola virus disease contacts Monoclonal antibodies (mAbs) appear to be interesting candidates for prophylaxis No contamination was found among contacts treated with mAbs Abstract: Introduction: With the development of therapeutics and vaccine against Ebola virus disease (EVD), the question of post-exposure prophylaxis for high-risk contact has emerged. Immunotherapies (monoclonal antibodies [mAbs]) recently validated for treating infected patients appear to be a good candidate for protecting contacts. Design: During the tenth EVD outbreak in the Democratic Republic of the Congo, we have administrated mAbs (Mab114 or REGN-EB3) to high and intermediate-risk contacts of EVD patients. Results: : Overall, 23 non-vaccinated contacts received mAbs after a median delay between contact and post-exposure prophylaxis of 1 day (interquartile range 1–2). All contacts were free of symptoms, and all had negative reverse transcriptase-polymerase chain reaction 14 days after the contact. Conclusion: Immunotherapies appear to be promising candidates to protect EVD contacts. Interaction with vaccine needs to be analyzed and a larger study on efficacy conducted.